Theoretical review of the psychological aspects of women's characteristics in the transport industry - Reyhan Akhmedova, Nigar Mirzaghayeva (Journal of Daoist Studies, 2026)
This research aims to evaluate how gender roles affect women's labor by articulating with the patriarchal social structure, and what stages women's labor has gone through in the world, through basic concepts and historical plane. The main claim of the study is that the biggest factor why doing a job that is attributed to men poses various difficulties for women is traditional gender roles. However, another claim of the study is that if positive discrimination principles are applied and equality of opportunity is provided, women can successfully perform the profession by overcoming the difficulties arising from gender roles. Working conditions within the scope of the research; It was evaluated together with data on wages, working hours and unionization. Physical and psychological disorders resulting from working life were examined specifically in the bus driving profession. The difficulties encountered in working life were analyzed on the basis of gender and the differences between being married and single women in working life. In the conclusion of the study, information about the theoretical discussion and data from the field research were synthesized. It draws attention to the importance of applying the principle of positive discrimination and providing equal opportunities for women in order to break down gender roles.